Horses of God [videorecording (DVD)] - Rashīd, ʻAbd al-Ḥakīm; Rashīd, ʻAbd al-Illah; Ṣuwīdiq, Ḥamzah ([Publisher not identified], 2014)
A fictional account of the lives of the men responsible for the suicide bombings in Casablanca in 2003.